PRAKTEK PEMBAGIAN WARISAN ANTARA ANAK LAKI-LAKI DAN ANAK PEREMPUAN DI KECAMATAN MARITENGNGAE KABUPATEN SIDRAP - RUKIAH, RUKIAH; ANWAR, WIRANI AISYAH (P3M STAIN Parepare, 2014)
This paper discusses about the system of division of inheritance in District Maritengngae Sidrap, implementation inheritance division between boys and girls in the District Maritengngae Sidrap, and the perspective of Islamic jurisprudence against the practice of inheritance in District Maritengngae Sidrap. Systems division of inheritance between boys and girls in the District Maritengngae Sidrap similar to that described in the Qurâan, which is 2: 1. Implementation inheritance division between boys and girls in the District Maritengngae Sidrap mostly do 1: 1 (the same versus).Islamic jurisprudence perspective to the practice of inheritance in District Maritengngae Sidrap listed in the Compilation of Islamic Law, which explained that the inheritance law has to be defnitive, ie 2: 1. three methods in diligence, namely: (1) Al-âAdah (habit). Guided from Abu Yusuf i.e. when a custom texts derived from the custom then turned and came new, then the law fall within the texts. During the traditions and texts are not in conï¬ict as a whole, so that the recognition of the tradition is seen as left and ignore texts. (2) Naskh. Nasakh is shifting or cancellation of laws or instructions contained in the verses received by the Prophet, In earlier times. Because nasakh indispensable for the beneft of the people then Munawir using this method. (3) Maslahah